Implementasi Metode Algoritma K-Means Clustering pada Toko Eidelweis - Reno Supardi; Indra Kanedi (Universitas Asahan, 2020)
Abstract - In making the application, the implementation of the K-Means Clustering Algorithm method at the Eidelweis Store will be designed for this study to design software at the Eidelweis Store. The method used in making this application is a system development method starting from problem determination, actual system analysis. , new system analysis, system design, system implementation, and system testing. In the implementation of the K-means Clustering algorithm method on the Eidelweis Store, the login menu, input menu, output menu and report menu, and main menu. In the main menu, there is a system that is connected to the next menu in the process to view reports about sales on taking Eideleweis easy to operate The results of the implementation process of the K-means Clustering algorithm method at Eidelweis Stores have been applied to the K-means Clustering method. The application of the K-means Clustering algorithm method in Eidelweis Stores is made using Visual Basic Net programming language with the SQL Server database.Keywords: K-means Clustering Algorithm Method, Visual Basic Net. Abstrak - Dalam Pembuatan Aplikasi Implementasi Metode Algoritma K-Means Clustering pada Toko Eidelweis akan dirancang tujuan penelitian ini adalah untuk membuat perancangan perangkat lunak software pada Toko Eidelweis, Metode yang gunakan pada pembuatan aplikasi ini adalah metode pengembangan sistem yang dimulai dari penentuan masalah, analisi sistem aktual, analisis sistem baru, perancangan sistem, implementasi system dan uji coba sistem. Dalam implementasi metode algoritma K-means Clustering pada Toko Eidelweis menu login, menu input, menu output dan menu laporan, menu utama. Pada menu utama terdapat sistem yang menghubungkan ke menu – menu selanjutnya dalam proses untuk melihat laporan tentang penjualan pada took Eideleweis mudah untuk dioperasikan. Hasil proses implementasi metode algoritma K-means Clustering pada Toko Eidelweis telah diterapkan metode K-means Clustering, Aplikasi implementasi metode algoritma K-means Clustering pada Toko Eidelweis dibuat dengan Bahasa pemrograman Visual Basic Net dengan database SQL Server.Kata Kunci : Metode Algoritma K-means Clustering, Visual Basic Net.